(untitled) (Journal of Surgical Sciences, 2020)
Background: Appendectomy, though being performed by both open and laparoscopic methods, there is a lack of consensus regarding which is the most appropriate method. This study will document important variables and parameters to compare therapeutic benefit of laparoscopic Appendectomy (LA) and open Appendectomy (OA). Objective: The study aimed at comparing the short- term outcome of laparoscopic Appendectomy and open appendectomy in cases of acute appendicitis, in terms of postoperative pain and complications, hospital stay, recovery and return to normal activities. Methods: Whenever there was clinical suspicion of acute appendicitis, the patient was admitted to hospital, relevant history was recorded and clinical examination was conducted, necessary laboratory and imaging studies were performed and patient satisfying the inclusion and exclusion criteria was included in the study. The Appendectomy procedure was attended by the investigator and all relevant perioperative data were recorded. Results: Post-operative pain was mostly mild in LA group (40%), while in OA, it was mostly severe (38%) and moderate (34%). Postoperative complications were significantly higher in OA than in LA. Hospital stay was longer in OA (7.03 days) than LA (3.49 days). Early recovery and return to full normal activity was noted in LA (5.56 days) than in OA (11.26 days). Moreover, operative time was shorter in LA (56.37 min), than in OA (71.86 min). Conclusion: Laparoscopic Appendectomy have clear advantages over open Appendectomy in respect to short term results. Journal of Surgical Sciences (2017) Vol. 21 (2): 70-75